ESTADO DE EXCEÇÃO E PODER JUDICIÁRIO: - Alex Cadier; Cristina Leite Lopes Cardoso (TRF2, 2020)
This article, through bibliographic review and jurisprudential analysis, discusses the reasons that identify the state of exception as a government paradigm and the judiciary acting as legitimizing this state, specifically in the context of criminal law. First, we will launch a look about biopolitics notions and the state of exception, showing how they apply to contemporary democratic societies. It will then be evident that the judiciary, rather than act as a counterpoint to the state of exception, in fact legitimizes, to also act selectively as the recipient of their decisions, which will become clear in the analysis of arguments used by the Supreme Court in the recent standardization of understanding of the consummation of the crime of theft, as opposed to extinction theory of punishment applied in general in tax crimes.